Paired Measurements of Paraoxonase 1 and Serum Amyloid A as Useful Disease Markers. (22nd October 2013) - Kotani, Kazuhiko; Yamada, Toshiyuki; Gugliucci, Alejandro
Abstract : Paraoxonase 1 (PON1) and serum amyloid A (SAA) are proteins carried by high-density lipoprotein (HDL) particles. Among the HDL-associated protein molecules, SAA, an inflammation-related marker, and PON1, an antioxidant marker, tend to change in relatively clear opposite directions in physiological situations. In clinical chemistry, paired measurements of both markers may provide useful information to understand dysfunctional HDL in diseases with inflammation and oxidative stress conditions. Actually, limited clinical studies have suggested that the combined use of PON1 and SAA may be a tool for observing the pathophysiology of some disease entities. From the findings of experimental studies, PON1 appears to be cooperatively regulated by inflammation- and oxidative stress-related molecules linked with SAA regulation in humans. More studies remain to be performed to ascertain the value of paired measurements of both promising markers in clinical practice.